2021
DOI: 10.1186/s12933-021-01425-0
|View full text |Cite
|
Sign up to set email alerts
|

Associations of hypoglycemia, glycemic variability and risk of cardiac arrhythmias in insulin-treated patients with type 2 diabetes: a prospective, observational study

Abstract: Background Insulin-treated patients with type 2 diabetes (T2D) are at risk of hypoglycemia, which is associated with an increased risk of cardiovascular disease and mortality. Using a long-term monitoring approach, we investigated the association between episodes of hypoglycemia, glycemic variability and cardiac arrhythmias in a real-life setting. Methods Insulin-treated patients with T2D (N = 21, [mean ± SD] age 66.8 ± 9.6 years, BMI 30.1 ± 4.5 kg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 56 publications
1
17
0
Order By: Relevance
“…In addition, we showed that atrial fibrillation was more commonly detected during hospitalization in patients with high GV than those with low GV among the patients without previously reported AF. This finding is in line with the previous studies that revealed cardiac arrhythmias were common in insulin-treated patients with type 2 diabetes and are associated with GV [29], which was also independently associated with the development of new-onset atrial fibrillation in these diabetic patients [30].…”
Section: Glycemic Variability In Cardiovascular Diseasessupporting
confidence: 93%
“…In addition, we showed that atrial fibrillation was more commonly detected during hospitalization in patients with high GV than those with low GV among the patients without previously reported AF. This finding is in line with the previous studies that revealed cardiac arrhythmias were common in insulin-treated patients with type 2 diabetes and are associated with GV [29], which was also independently associated with the development of new-onset atrial fibrillation in these diabetic patients [30].…”
Section: Glycemic Variability In Cardiovascular Diseasessupporting
confidence: 93%
“…(4,5) While there are different metrics representing glycemic variability in various aspects, the association between glycemic variability and severe hypoglycemia remains unclear because of the specific metrics applied in studies and heterogeneity of study design. Moreover, preventing hypoglycemia is prioritized by healthcare providers because it reduces the incidence of cardiac diseases, including cardiac arrhythmia and CVD ( 31 , 32 ). Future research could shift from emphasizing single metrics to combined glycemic-related metrics to improve the efficacy of predicting hypoglycemic events and reduce their occurrence.…”
Section: Discussionmentioning
confidence: 99%
“…Among the complications of type 2 diabetes, hypoglycemia is a common and potentially serious complication of diabetes [ 9 , 10 ] which can lead to cognitive dysfunction, hemiplegia, blurred vision, decreased renal function, arrhythmia, coma, and even death [ 11 ]. The definition of type 2 diabetes mellitus with hypoglycemia is a glucose alert value of 3.9 mmol/L (70 mg/dL) or less.…”
Section: Introductionmentioning
confidence: 99%